(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The latest Basel Accord, which relies on the New Capital Accord (i.e. Basel II) and whose basic goals have been, from a normative standpoint, enhancing the banking sector’s ability to absorb the losses arising from economic distresses like the global financial crisis (2007-2009), improving risk management and governance, and strengthening the bank’s transparency and disclosures, operationally emphasises the need to improve the quality and quantity of capital components, liquidity standards, and leverage ratio. The implementation of the Accord in developed economies started at the beginning of 2013 and the overall transition period from the Basel II framework should end by the year 2019. But as far as emerging economies are concerned, there are several issues on the road of implementation, such as necessary (technical) skills and expertise of bank staff as well as their supervisory institutions, sophisticated internal rating mechanisms and capacity, significant amount of new information and recordkeeping, etc. This paper discusses real and potential effects of Basel III in both developed and emerging economies. A special emphasis is given to the banking sector of Bosnia and Herzegovina. Keywords: International banking standards, Basel accords, Basel III, effects, developed economies, emerging economies, Bosnia and Herzegovina